“Oke, any questions?” The Questioning Interaction in an EFL Classroom - Fina Yanita; Yunisrina Qismullah Yusuf; Sofyan A. Gani (Proceedings of AICS - Social Sciences, 2016)
This study examined the teacher’s questioning interaction for meaning negotiation in an EFL classroom at a junior high school in Banda Aceh, Indonesia. Data was collected from an English teacher who was teaching seventh grade students. The instruments used were an observation sheet adapted from Arikan (2004), a set of interview questions adapted from Skilton and Meyer (1992) and Beutel (2010), and recordings. The questioning interaction was analyzed following on the three questioning devices: comprehension check, clarification check and confirmation check (Long, 1983). The findings showed that comprehension check was the most dominant device applied by the teacher (30%), followed by clarification check (14.3%), and confirmation check (12.8%). The dominant use of comprehension check in the classroom reflected the typical interaction in the EFL context, in which there was much more negotiation of meaning going on between the teacher and students to gain understanding. All of these devices were indicators of the students’ involvement in the classroom on negotiation and learning with the teacher. The result from the interview with the teacher further revealed that she must ask questions to know the students’ understanding of what is being learnt in class. By being aware of this, upcoming directions on her teaching to reach her teaching objectives can be made more effectively.